Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1073/pnas.89.21.10375
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in Drosophila embryos and L2 cells exhibit scavenger receptor-mediated endocytosis.

Abstract: Mammalian macrophage scavenger recep-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…We have shown that the shape of the dose-response curves for LDL and oxLDL induced MAPK activation was similar to the curve obtained for the binding/degradation of the radioiodinated lipoproteins. Although parameters obtained from degradation assays generally represent metabolism of the ligand at steady state rather than binding at equilibrium [33], the apparent dissociation constants determined at 37°C were found to be very similar to those determined for binding, uptake and degradation [34][35][36]. Hence, our data suggest a dose-response relationship of scavenger or apoB/E receptor binding/degradation and MAPK stimulation.…”
Section: Discussionmentioning
confidence: 59%
“…We have shown that the shape of the dose-response curves for LDL and oxLDL induced MAPK activation was similar to the curve obtained for the binding/degradation of the radioiodinated lipoproteins. Although parameters obtained from degradation assays generally represent metabolism of the ligand at steady state rather than binding at equilibrium [33], the apparent dissociation constants determined at 37°C were found to be very similar to those determined for binding, uptake and degradation [34][35][36]. Hence, our data suggest a dose-response relationship of scavenger or apoB/E receptor binding/degradation and MAPK stimulation.…”
Section: Discussionmentioning
confidence: 59%
“…Candidates could include Toll-like receptors or SRs on hemocytes or other cell types, as it is already known that apoLp-III is taken up by granular hemocytes (22), and that Drosophila cells appear to exhibit SR binding of ␤-glucans and other pathogen-associated molecular patterns (PAMPs) and endocytosis of modified LDL (50,51). In mammals, bacterial lipoproteins bind the Toll-like receptor 2, which is itself a pattern recognition receptor (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…8,25,26 However, not all Drosophila cell lines have endocytotic capability. 27 The fact that C6/36 cells are actively attracted to apoptotic cells and aggressively phagocytose fragmented apoptotic bodies suggests that this cell line, similar to the Drosophila S2 cell line, may have a mesoderm origin and display hemocyte/macrophage functionality.…”
Section: Resultsmentioning
confidence: 99%